Jerky seesaw nystagmus with internuclear ophthalmoplegia as the presenting finding in systemic lupus erythematosus - Çakır, Akın; Düzgün, Eyüp; Demir, Serkan; Aydın, Ali (Masson Editeur, 2014)
[Abstract Not Available]
Keywords: Systemic Lupus; Internuclear Ophthalmoplegia; Jerky Seesaw Nystagmus